Nursing Care For Children With Bronchopneumonia Diagnosion in Flamboyant Treatment Room - Nurmasita, Nurmasita; Sakriawati, Sakriawati; Sri Wahyuningsih; Durratul Fakhriyah; Anriani, Anriani (Journal of Islamic Nursing, 2024)
Bronchopneumonia is an inflammation of the respiratory tract that occurs from the bronchi to the alveoli. Bronchopneumonia is more common in young children and infants and is usually caused by the bacteria Streptococcus pneumonia and Hemofilus influenza. The aim of this study is to determine the nursing care and appropriate intervention for patients with a diagnosis of bronchopneumonia. The design of this research is a case study with a nursing process approach. The sample in this study was a child with the initials "A.". The research was carried out at the Flamboyan Kleas 3A RSUD Batara Siang nursing room in Pangkep district in 2023. Data collection is done through interviews, observations, and documentation studies. The research instrument uses the form of childcare foster care. The approach to the nursing process carried out by the researchers includes phases: the investigation of the researcher in collecting data, both from the patient and the patient's family and from the health care provider; performing nurses' diagnoses; nursed interventions; and implementation and evaluation of the nursery. The results of the evaluation in patients with Bronchopneumonia with a nursing diagnosis were: ineffective breathing patterns associated with depression of the respiratory center and inefficient breathing pathway cleanliness related to obstruction of the airway that occurred over three days as a whole. The conclusions obtained indicate the evolution of the patient's condition before and after the implementation. During the treatment, the family is expected to help in the healing process of the client by participating in the implementation of a nursing orphanage.